Grão de aveia preta em substituição ao grão de milho em dietas alto grão para produção de vitelos modificados da raça Jersey - Nascimento, Leandro Silva (2020)
The present study aimed to evaluate the effect of different levels of replacement (0, 38, 73 and 100%) of whole corn grain (Zea mays L.) for whole black oats grain (Avena strigosa Schreb) in high grain diets on the nutrients intake, animal performance, ingestive behavior and economic viability of the production of Jersey calves in feedlot. Twenty-four male castrated with an average initial body weight of 96 kg and an average initial age of 5 months were randomly distributed with six replications per treatment. The dry matter intake (DMI, kg/day), total digestible nutrients (TDNI, kg/day) and crude protein (CPI, kg/day) were higher (P<0.05) for diets with whole black oat grain in relation to the whole corn diet. When expressed in g/kg of body weight, DMI, TDNI and CPI not differ (P> 0.05) between diets. The neutral detergent fiber intake (NDFI kg/day and g/kg) was high (P<0,05) in the diets with whole black oat grain compared to the whole corn diet. The non-fibrous carbohydrates intake (NFCI, kg/day and g/kg) did not differ (P>0.05) between diets. The animals fed with black oat grain presented feces with greater consistency (P<0.05) in relation to the whole corn diet. The average daily gain was not influenced (P>0.05) by the levels of whole black oats grain in the diets. Feed conversion worsened with the increase in the proportion of whole black oats grain in the diets. The consistency of feces, assessed by the fecal score, was higher (P<0.05) in diets with black oats than in the corn based diet. The time of feeding, rumination and chewing/day were higher (P<0.05) in diets with black oat grain compared to the corn whole corn diet, while the time in other activities was shorter (P<0.05). Feeding efficiency decreased linearly (P<0.05) with increasing proportion of whole black oat grain in the diet. The number of chews per cake and the time of chewing per cake were not differ (P>0.05) by the proportion of the whole grain of black oats in the diets. The number of chewed/day was higher (P<0.05) for diets with black oat grain compared to whole corn diet. The dry matter rumination efficiency and neutral detergent fiber rumination efficiency were lower (P<0.05) for diets with whole black oat grain in relation to whole corn diet. The feeding cost was lower (P <0.05) in diets with whole black oat grain, while the cost of labor was higher (P <0.05) in relation to whole corn diet. Technical assistance costs, opportunity cost of invested capital, gross margin and net margin were not influenced (P>0.05) by diets. The effective and total operating costs were lower (P<0.05) in the whole black oat grain diets compared to the whole corn diet. The inclusion of whole black oats grain to replacement whole corn grain by up to 100% in the diet not alter the productive performance of Jersey calves produced in feedlot, which may reduce production costs.